2003
DOI: 10.1021/es025734l
|View full text |Cite
|
Sign up to set email alerts
|

Desorption Kinetics for Field-Aged Polycyclic Aromatic Hydrocarbons from Sediments

Abstract: This study considers desorption kinetics for 12 field-aged polycyclic aromatic hydrocarbons (PAHs) desorbing from size- and density-fractionated sediments collected from two locations in the New York/New Jersey Harbor Estuary. Desorption kinetics for PAHs with a log octanol-water partition coefficient greater than 6 were well-described by a one-domain diffusion model that assumes that PAHs are initially uniformly distributed throughout spherical sediment aggregates. PAH hydrophobicity and sediment specific sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
111
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 39 publications
(68 reference statements)
9
111
1
Order By: Relevance
“…Similarly, the desorption rates of DDT compounds from the heavy-density fraction of coarse-size sediment were extreme slow. This result was different from the previous observation that HOCs generally desorb faster from heavy-density and coarse size sediment than those from light-density and fine size sediment, because of generally lower TOC content and/or specific surface area for heavy-density and coarse size sediment (Shor et al, 2003). These findings suggested that the amounts of DDT compounds discharged from paint flakes to surface water are expected to be low.…”
Section: Desorption and Sorption Kinetics Of Ddt Compoundscontrasting
confidence: 95%
See 2 more Smart Citations
“…Similarly, the desorption rates of DDT compounds from the heavy-density fraction of coarse-size sediment were extreme slow. This result was different from the previous observation that HOCs generally desorb faster from heavy-density and coarse size sediment than those from light-density and fine size sediment, because of generally lower TOC content and/or specific surface area for heavy-density and coarse size sediment (Shor et al, 2003). These findings suggested that the amounts of DDT compounds discharged from paint flakes to surface water are expected to be low.…”
Section: Desorption and Sorption Kinetics Of Ddt Compoundscontrasting
confidence: 95%
“…For example, approximately 100% desorption of p,p'-DDE was achieved in 120 h for the 30e63 mm size fraction of heavy-density sediment from Site 2, but less than 50% desorption was achieved for the same fraction from Site 9. This was consistent with previous findings that the structure and density of organic matter can affect the behavior of HOCs (Shor et al, 2003;Wang et al, 2001). Only 1e10% of DDT compounds desorbed from paint flakes after 120 h of desorption, probably because DDT compounds were strongly bound to the paint matrix.…”
Section: Desorption and Sorption Kinetics Of Ddt Compoundssupporting
confidence: 92%
See 1 more Smart Citation
“…Researchers observed that heterogeneity in naturally occurring carbonaceous materials (CMs) caused sorption processes of hydrophobic organic compounds (HOCs) in sediments to occur as a combination of absorption into amorphous organic matter and adsorption onto condensed forms of CMs such as black carbon (BC), coal, and kerogen, collectively termed "carbonaceous geosorbents" (CG) (Allen-King et al 2002;Cornelissen et al 2005). Many studies reported that adsorption of PAHs onto CG can greatly affect their bioavailability and toxicity as "sequestration" of PAHs in sediments often takes place (Gustafsson et al 1997;Luthy et al 1997;Nam et al 1998;Rockne et al 2002;Shor et al 2003;Abu and Steve 2005).…”
Section: Introductionmentioning
confidence: 99%
“…All but one of these models requires at least two (mathematical) compartments to fit the experimental data. These compartments can then define a combination of an instantaneous compartment where no mass transfer limitation is assumed with a dynamic compartment where mass transfer is limited (Ball and Roberts 1991;Sabbah et al 2005), two dynamic compartments (Brusseau et al 1991;Weber et al 1992;Xing and Pignatello 1996;Cornelissen et al 1998;Ghosh et al 2000;Shor et al 2003;Gamst et al 2004) or a continuum of compartments with various parameters (Culver et al 1997;Werth et al 2000;Werth and Hansen 2002). Although sometimes excellent fits of experimental and modeled data were demonstrated in the different papers, the physical explanation of the desorption process and its limitations is only briefly elaborated and do not include the effect of particle-size distribution.…”
Section: Introductionmentioning
confidence: 99%